2023
DOI: 10.3389/fphys.2023.1163947
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ocular surface assessment outcomes between healthy controls and patients with obstructive sleep apnea–hypopnea syndrome: a meta-analysis of the literature

Abstract: Objective: This meta-analysis aims to determine whether ocular surface alterations are associated with disease severity in patients with obstructive sleep apnea–hypopnea syndrome (OSAHS).Methods: The protocol for this systematic review and meta-analysis was registered in PROSPERO. We conducted the search in six electronic databases (China National Knowledge Infrastructure, EMBASE, Cochrane Library, Web of Science, Wanfang, and PubMed) from since the construction of the databases to 30 December 2022. The standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
1
0
0
Order By: Relevance
“…In our study, the OSDI scores in mild & moderate and severe OSAS groups were significantly higher (p < 0.05) compared to the control group. Similar findings were reported in previous studies by Jian Sun et al (21), Qi Pu et al (22), and Mutlu Acar et al (9), who found that severe OSAS cases had high scores in OSDI questionnaire. Another study found a positive correlation between high OSDI scores and low TBUT (9).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the OSDI scores in mild & moderate and severe OSAS groups were significantly higher (p < 0.05) compared to the control group. Similar findings were reported in previous studies by Jian Sun et al (21), Qi Pu et al (22), and Mutlu Acar et al (9), who found that severe OSAS cases had high scores in OSDI questionnaire. Another study found a positive correlation between high OSDI scores and low TBUT (9).…”
Section: Discussionsupporting
confidence: 91%